Understanding Criminal Behaviour: Psychosocial Approaches on Criminality to Violence - Jones, David Wyn (2020)
This is a second edition written in responses to the first edition that made it clear that there is an appetite for a better understanding of criminal behaviour that crossed traditional disciplinary boundaries and allowed for an understanding of the emotional worlds of human beings to be thought of alongside issues of social conditions. The most important changes introduced in this second edition are the addition of two new chapters. The first of these (Chapter 9 Public Violence and Crimes of Terror) presents the case for there being a growing category of offending that can be described as ‘public violence’. It is suggested that it is worth distinguishing crimes of violence that are aimed at or are initiated within the public sphere. Included here are the categories of ‘celebrity assassination’, ‘school shootings’ and violent acts of ‘extremism’. The second wholly new addition is Chapter 10 on the topic of ‘‘’Race’ and crime”. Neither of these chapters were easy to write. The first is inspired by the growing impact of, and interest in acts of terror. I had formerly taken the view that acts of terrorism were simply better understood in terms of politics and geopolitical events. The events of the 21st century, with large numbers of people being slaughtered by acts of ‘terror’ and in response to those acts, have meant it was now longer tenable to side-step the issue. It did seem to be clear that people’s feelings and understandings of events seemed as important as the events themselves. The continuing misery associated with the ‘problem’ of ‘race’ in the criminal justice system has overcome my reluctance as a white academic to engage with the problem. It was no longer credible, or right, to stand aside on the issue. Both of these chapters take a very overt psychosocial approach. It has become clearer to me since the first edition that this approach needs to be one that could be rooted in historical understanding. It is simply impossible to understand a topic like ‘race’ without thinking very hard about historical processes that have created the categories that cause such pain. Chapter 1 now presents a more explicit theoretical exposition of the meaning of a ‘psychosocial criminology’ and its cross-disciplinary nature. It is not only the integration of psychological theorisation with sociological and cultural analysis; the importance of a historical understanding is also emphasised here. My indebtedness to Norbert Elias’s work on the entwinement of large scale social changes occurring over long periods of time and the subjective mental states of individuals is made clear. Chapter 2, on the significance of mental disorder has been updated and is expanded. I have become more convinced that there is a very wide border between issues of mental health and the criminal justice system and that there are very important messages here about the demands that are being made of us in contemporary times, and the problems that can create. Again, the historical roots of this need to be thought about, and the historical section of the chapter has been expanded. There more minor updates throughout the rest of the book